2011
DOI: 10.1186/1471-2458-11-439
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the non-work determinants of workers' mental health? A systematic review of longitudinal studies

Abstract: BackgroundIn the past years, cumulative evidence has convincingly demonstrated that the work environment is a critical determinant of workers' mental health. Nevertheless, much less attention has been dedicated towards understanding the pathways through which other pivotal life environments might also concomitantly intervene, along with the work environment, to bring about mental health outcomes in the workforce. The aim of this study consisted in conducting a systematic review examining the relative contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 130 publications
10
62
0
5
Order By: Relevance
“…Qualitative analyses of participant problems indicated that problems from both the work and nonwork domains were reported and addressed during the intervention. This result supports findings emphasizing the importance of non-work determinants for the prediction of a worker's mental health (56). The changes in depressive symptoms correspond to results from earlier studies of worker-directed interventions, which had effect sizes of d=0.13 (24), d=0.20 (23), d=0.40 (12), and d=0.82 (22) when targeting employees with heightened levels of occupational stress.…”
Section: Discussionsupporting
confidence: 86%
“…Qualitative analyses of participant problems indicated that problems from both the work and nonwork domains were reported and addressed during the intervention. This result supports findings emphasizing the importance of non-work determinants for the prediction of a worker's mental health (56). The changes in depressive symptoms correspond to results from earlier studies of worker-directed interventions, which had effect sizes of d=0.13 (24), d=0.20 (23), d=0.40 (12), and d=0.82 (22) when targeting employees with heightened levels of occupational stress.…”
Section: Discussionsupporting
confidence: 86%
“…It should be noted that the major determinants of health and quality of life in economically active population include non-occupational factors, such as: family, network and community or society-level aspects. The systematic review of published data has shown that the nonoccupational domain is a largely underinvestigated area of workers' mental health research [19]. The highest levels of dissatisfaction in the environmental quality of life were closely related with both poor financial position and limited access to health services.…”
Section: Discussionmentioning
confidence: 99%
“…Job strain has well documented Archived at the Flinders Academic Commons: http://dspace.flinders.edu.au/dspace/ effects on psychological and physical health and is a putative mediator. (23) As mentioned above, buffers against insecurity and strain may be found in social support in the workplace, (24) and perceived employability. (25) However, the inequities of nonstandard employment are often exacerbated because those workers tend to have lower education, be in low skill occupations and lack the previously mentioned resources.…”
Section: Pathways From Nonstandard Employment To Healthmentioning
confidence: 99%